Geology of the northern Convoy Range, Victoria Land, Antarctica. Issue 2 (9th December 2020) - Capponi, Giovanni; Montomoli, Chiara; Casale, Stefano; Simonetti, Matteo
ABSTRACT: In this paper, we supply a geological map of the area between 76°–76°30′S and 159°–163°E, that was the only missing portion to complete an entire coverage of Victoria Land, filling the gap between the GIGAMAP program (to the north) and the maps by the New Zealand Antarctic program (to the south). The mapped area encompasses an early Paleozoic basement, and a flat-lying cover of sedimentary and igneous rocks, Permo-Triassic to Jurassic in age. The basement consists of large bodies of the Granite Harbour Igneous Complex, a granitic complex linked to the Ross Orogeny. After the early Paleozoic Ross Orogeny, the area was uplifted and eroded, and the sandstones of the Beacon Supergroup were deposited on the resulting erosion surface. The Beacon Supergroup sandstones were in turn covered and in most cases incorporated into the volcanic and sub-volcanic rocks of the Jurassic Ferrar Group.